Atorvastatin protects against liver and vascular damage in a model of diet induced steatohepatitis by resetting FXR and GPBAR1 signaling. Issue 1 (4th December 2021) - Marchianò, Silvia; Biagioli, Michele; Roselli, Rosalinda; Zampella, Angela; Di Giorgio, Cristina; Bordoni, Martina; Bellini, Rachele; Morretta, Elva; Monti, Maria Chiara; Distrutti, Eleonora; Fiorucci, Stefano
Abstract: Farnesoid‐x‐receptor (FXR) agonists, currently trialed in patients with non‐alcoholic steatosis (NAFLD), worsen the pro‐atherogenic lipid profile and might require a comedication with statin. Here we report that mice feed a high fat/high cholesterol diet (HFD) are protected from developing a pro‐atherogenic lipid profile because their ability to dispose cholesterol through bile acids. This protective mechanism is mediated by suppression of FXR signaling in the liver by muricholic acids (MCAs) generated in mice from chenodeoxycholic acid (CDCA). In contrast to CDCA, MCAs are FXR antagonists and promote a CYP7A1‐dependent increase of bile acids synthesis. In mice feed a HFD, the treatment with obeticholic acid, a clinical stage FXR agonist, failed to improve the liver histopathology while reduced Cyp7a1 and Cyp8b1 genes expression and bile acids synthesis and excretion. In contrast, treating mice with atorvastatin mitigated liver and vascular injury caused by the HFD while increased the bile acids synthesis and excretion. Atorvastatin increased the percentage of 7α‐dehydroxylase expressing bacteria in the intestine promoting the formation of deoxycholic acid and litocholic acid, two GPBAR1 agonists, along with the expression of GPBAR1‐regulated genes in the white adipose tissue and colon. In conclusion, present results highlight the central role of bile acids in regulating lipid and cholesterol metabolism in response to atorvastatin and provide explanations for limited efficacy of FXR agonists in the treatment of NAFLD.